2011
DOI: 10.1080/13607863.2011.583628
|View full text |Cite
|
Sign up to set email alerts
|

The Enriched Opportunities Programme for people with dementia: A cluster-randomised controlled trial in 10 extra care housing schemes

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
95
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(99 citation statements)
references
References 12 publications
4
95
0
Order By: Relevance
“…Furthermore, many of the included studies used 'ideal type' interventions, including intensive service provision involving a range of professionals (all the UK studies), while the two Finnish studies applied health interventions to augment standard social care for people with dementia. In spite of their benefits, these types of intervention may be more costly to provide (Brooker et al, 2011) and financially unsustainable in the long term (Challis et al, 2002;Gladman et al, 2007). Such issues of cost are also relevant to the type of research design adopted and the different criteria used in determining the success of the intervention being evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, many of the included studies used 'ideal type' interventions, including intensive service provision involving a range of professionals (all the UK studies), while the two Finnish studies applied health interventions to augment standard social care for people with dementia. In spite of their benefits, these types of intervention may be more costly to provide (Brooker et al, 2011) and financially unsustainable in the long term (Challis et al, 2002;Gladman et al, 2007). Such issues of cost are also relevant to the type of research design adopted and the different criteria used in determining the success of the intervention being evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Many references were excluded because they had an inadequate focus on social support at home for people with dementia (130). A further two studies (Brooker et al, 2011;Riordan and Bennett, 1998) were identified and added by the team. This was because they were considered to be relevant to the review.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations